2005
DOI: 10.1016/j.joca.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based biomarkers for detecting mild osteoarthritis in the human knee

Abstract: Linear combinations of blood RNA biomarkers offer a substantial improvement over currently available diagnostic tools for mild OA. Blood-derived RNA biomarkers may be of significant clinical value for the diagnosis of early, asymptomatic OA of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 41 publications
0
25
1
1
Order By: Relevance
“…Both proteins showed a considerable fold change in our analysis (1.8 and 3, respectively), and had a considerable number of interacting partners in the network analysis (six and seven, respectively) suggesting that expression changes are likely to have a substantial impact on cellular processes including apoptosis. Also MAFB and EGR1 , identified previously as biomarkers in blood expression profiles of patients with mild knee osteoarthritis,34 were differentially expressed in our dataset. Taken together, the overlap between our analysis and other studies confirms that osteoarthritis-specific gene expression profiles of PBMC exist.…”
Section: Discussionmentioning
confidence: 70%
“…Both proteins showed a considerable fold change in our analysis (1.8 and 3, respectively), and had a considerable number of interacting partners in the network analysis (six and seven, respectively) suggesting that expression changes are likely to have a substantial impact on cellular processes including apoptosis. Also MAFB and EGR1 , identified previously as biomarkers in blood expression profiles of patients with mild knee osteoarthritis,34 were differentially expressed in our dataset. Taken together, the overlap between our analysis and other studies confirms that osteoarthritis-specific gene expression profiles of PBMC exist.…”
Section: Discussionmentioning
confidence: 70%
“…Unsupervised clustering demonstrated that while contralateral samples were different from shamoperated samples, heterogeneity among contralateral samples was present, with some animals showing greater dysregulation than others. Differences in gene expression in the contralateral and sham-operated samples could be due to altered biomechanics (e.g., altered loading of the contralateral joint) or to systemic factors (e.g., mediators of inflammation) released as OA progresses in the ipsilateral joint (57). Further, differences in compensatory contralateral joint loading between individuals may account for heterogeneity among contralateral samples.…”
Section: Discussionmentioning
confidence: 99%
“…Using a genomic approach based on isolation of mRNA from circulating blood and subsequent reverse transcription polymerase chain reaction, Marshall et al [2] identified six genes which were significantly downregulated in patients with mild osteoarthritis (according to arthroscopy assessment) compared with healthy controls. Combination of these six genes in a multiple variable model was able to correctly identify 85% with mild osteoarthritis and controls.…”
Section: New Methodologies and New Biochemical Markersmentioning
confidence: 99%